Recurrent WNT pathway alterations are frequent in relapsed small cell lung cancer - Alex H. Wagner (Nature Portfolio, 2018)
Small cell lung cancer (SCLC) patients frequently relapse and become resistant to chemotherapy. Here, the authors analyse the genomic and transcriptomic landscape of primary and relapsed SCLC patients as well as in vitro models, and discover that activation of WNT signalling can drive chemotherapy resistance.